Developing Principles for the Regulation of Microinsurance (Philippine Case Study) - Gilberto M. Llanto; Maria Piedad S. Geron; Joselito Almario (Philippine Institute for Development Studies (PIDS), 2007)
Low-income households find it hard to cope with the risks brought about by an illness or injury, death of a family member, man-made calamities, and natural disasters. Demand for microinsurance products is growing and both formal and informal microinsurance schemes have started to emerge to address this need. This paper seeks to provide a better understanding of the microinsurance market in the Philippines and to draw certain principles for microinsurance regulation from a review of the Philippine experience with microinsurance. The Philippine experience on the provision of microinsurance services and the interaction between the insurance providers and the regulator may help inform the development of certain principles for microinsurance regulation.
Keywords: 330; regulatory framework; microinsurance; mutual benefit associations; Insurance Commission; risk protection; partner agent approach; Versicherungsschutz; Mikrofinanzierung; Marktmechanismus; Regulierung; Prinzipal-Agent-Theorie; Philippinen